2022
DOI: 10.1021/acs.jafc.2c02534
|View full text |Cite
|
Sign up to set email alerts
|

Construction, Pesticidal Activities, Control Effects, and Detoxification Enzyme Activities of Osthole Ester/Amide Derivatives

Abstract: Pesticide research and development has entered an era of safety, efficiency, and environmental friendliness. Discovery of effective active products directly or indirectly from plant secondary metabolites as pesticide candidates has been one of the current research focuses. Herein, two series of new ester and amide derivatives were prepared by structural modifications of a natural coumarin-type product osthole at its C-4′ position. Their structures were characterized by IR, mp, 1H NMR, and HRMS. Confirmation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 37 publications
0
19
0
Order By: Relevance
“…The control efficiency of compounds 1 and 4f against T. cinnabarinus was evaluated in the greenhouse. , …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The control efficiency of compounds 1 and 4f against T. cinnabarinus was evaluated in the greenhouse. , …”
Section: Methodsmentioning
confidence: 99%
“…The acaricidal activity of compounds 1 – 3 , 4a – z , and 4a′ – c′ against T. cinnabarinus was evaluated by the slide-dipping method. , …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Then, in the presence of NaBH 4 and MeOH, compound 2 was reduced to give compound 3 [ 45 ]. Finally, in the presence of EDCI and DMAP, target compounds 4–12 were obtained by reaction of compound 3 with aromatic acids RCO 2 H in 44–57% yields [ 46 , 47 ]. The chemical structures of compounds 2–12 were all determined by mp, IR, 1 H NMR, and 13 C NMR.…”
Section: Resultsmentioning
confidence: 99%
“…Particularly, compounds 9 and 11 were 45.4– and 47.6–fold stronger than piperine. Notably, their acaricidal activities were more potent than those of 7-oxycarbonylandrographolide, cholesterol, and osthole ester/amide derivatives [ 38 , 41 , 45 , 46 ]. When compared with our previous results [ 48 ], it suggested that introduction of the CH 2 between the phenyl/4-Fphenyl/4-Clphenyl and the carbonyl groups was very important for the acaricidal activity.…”
Section: Resultsmentioning
confidence: 99%